Research on an All-Flow Velocity Control Strategy for a 120 kW Variable-Pitch Horizontal Axis Tidal Current Turbine - Wang, Bingzhen; Ke, Wei; Zhang, Yuanfei; Duan, Yunqi (Journal of marine science and engineering, 2022)
Horizontal-axis tidal current turbines have considerable potential to harvest renewable energy from ocean tides. The pitch control system is a critical part of variable-pitch tidal turbines. Existing control strategies for tidal turbines mainly rely on flow measurement devices to obtain tidal velocities, which are costly and subject to many limitations in practical applications, making them unsuitable for small off-grid tidal turbines. In this paper, we propose a pitch control strategy for a 120 kW horizontal-axis tidal current turbine based on the output power of the generator. The torque of the turbine was calculated based on the blade element momentum theory, and a dynamic model of the tidal turbine was established. The dynamic characteristics of the turbine and generator were studied under various flow rates and pitch angles. On the basis of the characteristic analysis, the generating efficiency of the unit was improved under a low flow rate, and the output power was limited to a rated value under high-current velocity by regulating the pitch angle. Furthermore, a novel protection and start up strategy is proposed to protect the unit and make full use of the tidal energy when the tidal current velocity exceeds the limit value. We performed simulations, the obtained results of which demonstrate the effectiveness and advantages of the designed control strategies.